Genetic diversity and population structure of penis fish (Urechis unicinctus) based on mitochondrial and nuclear gene markers. (17th November 2018) - Gong, Jie; Zhao, Ruoping; Deng, Jiaheng; Zhao, Yancui; Zuo, Jincheng; Huang, Ling; Jing, Meidong
Abstract: Urechis unicinctus is distributed only in Bohai Gulf of China and Korean and Japanese coast. The wild populations of this species have sharply declined in China and Japan. We collected 105 samples from six localities of Bohai Gulf and Korea coast, and investigated genetic diversity and population structure with mitochondrial COI, 16S-rRNA and nuclear 28S-rRNA gene fragments. Genetic diversity of U. unicinctus based on COI sequences was still high (Hd: 0.9595, π: 0.0101), however, 28S-rRNA gene sequences showed low level of genetic diversity (Hd: 0.4084, π: 0.0007). Based on COI sequences, F ST values between populations ranged from −0.00204 to 0.05210, and 99.12% genetic diversity was contributed by different individuals within population. Both phylogenetic trees and median-joining network did not show clear geographic cluster, haplotypes from different populations were mixed. Our results indicated low level of genetic divergence among different localities of U. unicinctus, and this species should be treated as a whole population among China, Japan and Korea coast during species conservation.